2011
DOI: 10.1021/ma202268j
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Free-Standing Polymer Films Deposited onto Patterned Ionic Liquids and Silicone Oil

Abstract: We studied the vapor deposition of polymers onto the surfaces of silicone oil and imidazolium-based ionic liquids (ILs). We found that the deposition of poly(2-hydroxyethyl methacrylate) (PHEMA) and poly(N-isopropylacrylamide) (PNIPAAm) resulted in polymer particles on silicone oil whereas continuous polymer skins formed on 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF 6 ]), 1-butyl-3-methylimidazolium tetrafluoroborate ([bmim][BF 4 ]), and 1-ethyl-3-methylimidazolium tetrafluoroborate ([emim][BF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Besides solid substrates, Gupta and co‐workers have shown that iCVD is able to coat liquids with low vapor pressure, for example, ionic liquids (ILs) 145. Surfaces patterned with IL and silicone oil resulted in the selective encapsulation of IL, given that continuous iCVD films can only be deposited on ILs but not on silicone oil 146. In addition, marbles of IL were fully encapsulated within a polymer shell of p(PFDA‐ co ‐EGDA) 147.…”
Section: Chain Growth Polymerization: Icvdmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides solid substrates, Gupta and co‐workers have shown that iCVD is able to coat liquids with low vapor pressure, for example, ionic liquids (ILs) 145. Surfaces patterned with IL and silicone oil resulted in the selective encapsulation of IL, given that continuous iCVD films can only be deposited on ILs but not on silicone oil 146. In addition, marbles of IL were fully encapsulated within a polymer shell of p(PFDA‐ co ‐EGDA) 147.…”
Section: Chain Growth Polymerization: Icvdmentioning
confidence: 99%
“…Free‐standing p(PFDA) polymer films have been obtained by depositing the iCVD polymer over droplets of ionic liquid 146. The low surface energy p(PFDA) coatings have been applied on PDMS‐based micromold173 and microfluidic88 devices in order to create a barrier coating towards organic solvents.…”
Section: Fluoropolymersmentioning
confidence: 99%
“…They could also potentially be prepared using free-standing, iCVD polymer films [34]. This type of membrane could have permeability that increases with ro/rt according to Eq.…”
Section: Effect Of Icvd Films On Membrane Permeabilitymentioning
confidence: 99%
“…Since porous substrates do not allow using physical mask, metal salts were printed on the membranes inhibiting the polymerization process and thus, creating the pattern [44]. Ionic liquids (IL) were also modified using iCVD p(PFDA) [45,46]. Due to the low vapor pressure of IL, the PFDA monomer is able to adsorb on its surface and encapsulate the IL.…”
Section: Poly(1h1h2h2h-perfluorodecyl Acrylate)mentioning
confidence: 99%